Regional Disparities, Growth, and Inclusiveness. (IMF Working Papers; Working Paper ;, 2021)
We discuss regional disparities in economic performance and living standards. We first set out some key facts, and provide a conceptual framework to help analyze whether such disparities are efficient, or instead reflect market and/or policy failures. We examine whether policy attempts to reduce regional disparities necessarily involve a trade-off between equity and efficiency. We then investigate whether policymakers should focus on boosting the economic performance of lagging regions-or, conversely, accept the presence of regional disparities, and instead assist households in lagging regions through transfer payments, investments in education, health, and other basic services, and by facilitating out-migration.